2020
DOI: 10.1111/ases.12819
|View full text |Cite
|
Sign up to set email alerts
|

Video‐assisted thoracoscopic right upper lobectomy in a patient with a displaced bronchus and vascular abnormalities

Abstract: Bronchial abnormalities are rare, and they are infrequently associated with pulmonary vascular abnormalities. It is important to identify such abnormal anatomical structures before lobectomy of the lung under thoracoscopy. There have been only three reports on video-assisted thoracoscopic lobectomy in patients with anomalous bronchi and vascular abnormalities to date. Here, we present a report of video-assisted thoracoscopic right upper lobectomy per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several studies have reported absence of the right SPV at the anterior hilum with an anomalous V1-V3 segment that passes between the PA and the bronchus [11][12][13][14][15][16][17]. To our knowledge, only eight studies have reported right upper lobe resection for lung cancer in patients with concomitant ectopic variation of the right SPV and RUB (Table 1) [11,12,14,[18][19][20][21][22].. The site of the right SPV and the RUB in our patient differed from sites observed in patients described by previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have reported absence of the right SPV at the anterior hilum with an anomalous V1-V3 segment that passes between the PA and the bronchus [11][12][13][14][15][16][17]. To our knowledge, only eight studies have reported right upper lobe resection for lung cancer in patients with concomitant ectopic variation of the right SPV and RUB (Table 1) [11,12,14,[18][19][20][21][22].. The site of the right SPV and the RUB in our patient differed from sites observed in patients described by previous studies.…”
Section: Discussionmentioning
confidence: 52%
“…Cases of bronchial bifurcation are often accompanied by pulmonary artery bifurcation abnormalities and lobular insufficiency [ 4 , 5 ]; therefore, careful preoperative scrutiny is essential. In this case, bronchoscopy was performed preoperatively in both cases and bronchial branching abnormalities could, therefore, be determined accurately.…”
Section: Discussionmentioning
confidence: 99%